The Development of B-Adrenergic Blocking Drugs for Management of Primary Open-Angle Glaucoma - Doughty, M.J; Lyle, W.M (Canadian Journal of Optometry, 2021)
In the last few years, there has been a marked increase in the number of drugs available for the management of open-angle glaucoma. The development of these newer ophthalmic drugs has been prompted by a desire to make available, to the public, products that display maximum efficacy (with respect to the glaucoma) but minimal side effects on the body generally or on the health of the eye or on vision. The major development has been in a set of drugs active on B-adrenergic receptors (the B-blockers"). While many of these newer drugs are, as yet, available only in Europe or Japan, in 1986, three new ophthalmic B-blockers became available in the English-speaking world. It is our intent in this article to review why there has been this major expansion in the number of drugs available to manage glaucoma or ocular hypertension...